Evolution of durability and mechanical properties of ordinary portland cement concretes in sulphates attack - Narimane, Zaidi (Array, 2020)
Concrete in sulphates environments often undergoes significant alterations that often have significant adverse results on its engineering properties. However, the choice of cement type is a very important factor for concrete exposed in aggressive environment. This research presents the effect of two types of cement on the mechanical and microstructure properties of ordinary concretes exposed in aggressive solution dosed with 5% of gypsum (Ca2SO4.2H2O). The tests studied in this experimental part were the compressive strength, flexural strength, thermogravimetry, mercury intrusion porosimetry and mass variations of the concrete. The results clearly show that the CEM I 42.5 is suitable for the formulation of concretes exposed to sulphate attack and their properties are better compared with the CEM II/A 42.5.